Neuroplasticidade induzida pelo "status epilepticus" em ratos normonutridos e desnutridos - Gustavo Henrique de Souza e Rezende (2006)
Neonatal undernutrition plays a significant role on morphology and physiology of the developing central nervous system (CNS), leading, frequently, to permanent alterations. These alterations are highly injurious when occur in the period of neurogenesis, including axonal sprouting. To investigate the effect of neonatal undernutrition onneuroplasticity of the CNS, promoted by the status epilepticus provoked by pilocarpine,four groups of Wistar rats wereused.Wellnourished group (WNG) fed ad libitum lab chow diet supplemented with 25% dog food; Undernourished group fed 60% of the amount o diet consumed by WNG; The wellnourished and undernourished groups were subdivided: one wellnourished group (WNGP) and one undernourished group (UNGP), at 45 days of life, were submitted to status epilepticus by pilocarpine induction (320mg/kg i.p.) 30 minutes after the administration of methyl-scopolamine (1,0 mg/kg i.p.). After 90 minutes in status epilepticus, the seizures were aborted with Diazepam NQTM(20 mg/kg). The control groups (WNG and UNG) had the same treatment, but saline injection replaced pilocarpine. After a recovery period, the animals were filmed daily for a period of 6 hours. At 120 days of life electroencephalography was registered and then the rats were sacrificed to measure DNA, proteins, glutamate release from hippocampus and Neo-Timm staining of the hippocampus granule cells sprouting. No difference was observed in the latenc y of the beginning of the spontaneous recurrent seizures (SRS), neither in the daily quantity of seizures between the WNGP and UNGP. However, it was observed longer lasting time of the SRS in the WNGP when compared to UNGP, but this difference was not observed for epileptiform EEG-register in thisgroups. The WNG and UNG did not present SRS. The food restriction model used decreased body mass from 7th day of life and brain mass at the sacrifice. No differences were found in the amount of proteins and DNA content in samples from hippocampus tissues of WNG and UNG controls or pilocarpine-treated. The amount of glutamate released, stimulated by K+, was greater in the hippocampus slices of WNGPthan in others studied groups. Also, it was found higher intensity of the mossy fibers sprouting of the granule cells of the hippocampus in WNGP than in the UNGP,assessed by Neo-Timm. The WNG and UNG groups did not present sprouting. The results indicate decreased neuroplasticity, due to nutritional insult, in the epilepsy model promoted by systemic injection of pilocarpine.Key words: Under-nutrition, neuroplasticity, sprouting and epilepsy.